2017
DOI: 10.1021/acs.energyfuels.6b03220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organics and Carbonates on the Oxidation and Precipitation of Iron during Hydraulic Fracturing of Shale

Abstract: Hydraulic fracturing of unconventional hydrocarbon reservoirs is critical to the United States energy portfolio; however, hydrocarbon production from newly fractured wells generally declines rapidly over the initial months of production. One possible reason for this decrease, especially over time scales of several months, is the mineralization and clogging of microfracture networks and pores proximal to propped fractures. One important but relatively unexplored class of reactions that could contribute to these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
219
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(230 citation statements)
references
References 39 publications
11
219
0
Order By: Relevance
“…The low pH of NR-PF and HPT-PF is a common observation amongst HFF used in the Marcellus Shale region (Jew et al, 2017). HCl is a common additive used to prevent scaling of secondary minerals and was also used in creating the synthetic HFF used in this study.…”
Section: Discussion 241 Aqueous Inorganic Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The low pH of NR-PF and HPT-PF is a common observation amongst HFF used in the Marcellus Shale region (Jew et al, 2017). HCl is a common additive used to prevent scaling of secondary minerals and was also used in creating the synthetic HFF used in this study.…”
Section: Discussion 241 Aqueous Inorganic Chemistrymentioning
confidence: 99%
“…In some cases, the shale acts as a buffering agent with increasing amounts of carbonate material and calcite dissolution. Previous fluid-rock reaction studies, conducted at ambient pressures, have shown that the dissolution or precipitation of iron bearing minerals is dependent upon dissolved organic compounds, carbonate content of the shale during (buffering capacity) and the overall pH of the system (Harrison et al, 2017, Jew et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…to [17]. In general, the average first year decline in natural gas production rates across Pennsylvania resemble a hockey stick ( Figure 5) with the drop off ranging from 60 to 80 percent.…”
Section: Introductionmentioning
confidence: 94%
“…The Susquehanna River Basin is in essence "the canary in the coal mine". If the rapid depletion of fracked well production after the first year and the predictions for growing demand to support natural gas pipeline shipments globally hold sway, the Basin is only in the early stages of development and thousands more wells will be drilled and fracked [17]. Conversely, if technological innovations lead to increased production from refracturing existing wells, then the industrialization of the Susquehanna River Basin could be reduced [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation